(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
A series of specialist reports on fish, mammal, bird, amphibian bones, marine shells and plant remains from the caves forming the Geodha Smoo. The evidence seems to favour fishing for consumption in the caves rather than for the preservation and consumption of the fish elsewhere. The marine shells indicate the use of molluscs for quite specific purposes with each cave demonstrating a different use, as a food resource, for fishing bait and the extraction of purple dye. This combined with the evidence of the plant remains suggests an economy seeking to support itself on a local scale, possibly supplemented later by grain and other goods transported over short distances.